Vysoká laterální valgizační osteotomie bérce - technika "closed-wedge" - Lenz, David; Šmíd, Zdeněk (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2012)
PURPOSE OF THE STUDY The aim of the study was to evaluate the group of patients treated for varus arthritic knee by the method of high tibial osteotomy from the lateral approach and to assess its role in the present-day orthopaedic surgery which also offers other options such as distraction osteotomy from the medial approach, autologous chondrocyte transplantation or alloplasty. MATERIAL AND METHODS The study included 101 patients, 41 women and 60 men, undergoing lateral valgus high tibial osteotomy at our department between 2003 and 2007. The age of patients at the time of surgery ranged from 34 to 61 years, with an average of 54 years. The follow-up period was in the range of 2 to 7 years, with an average of 5.2 years. Moderate varus gonarthrosis was the most frequent indication for osteotomy. Each procedure was preceded by arthroscopy with treatment of the pathologies found; these most frequently included a torn medial meniscus, synovitis or medial compartment chondropathy The outcomes were evaluated using a system of clinical and radiographic assessment (A) and the Lysholm score (B) before and after surgery. RESULTS The A system evaluation showed excellent, good and poor results in 42, 47 and 12 patients, respectively. The average Lysholm score was 51 points before surgery and 73 points at the final follow-up examination; the average improvement was by 22 points. The average mechanical axis was 2 degrees of varus before and 6 degrees of valgus after surgery. The minimal correction of the axis was 4 degrees and the maximal correction was 18 degrees. The average change of the axis was 8 degrees. Complications were recorded in 21% of the patients. None of the patients had delayed healing, pseudo-arthrosis, fracture of the tibial plateau or peroneal nerve palsy. DISCUSSION Long-term excellent and good outcomes were found more often in the patients with a greater resulting valgus angle. After surgery the average anatomical axis was 7.4 degrees of valgus for good and excellent results, and 4.3 degrees of valgus for poor results. This is in agreement with the common recommendation that osteotomy should produce mild over-correction. The 95% osteotomy survival rate in this study is in accordance with the results reported by Coventry et al. and Sprenger et al. With strict adherence to the indication criteria, we did not find any clear relationship between the severity of knee injury before surgery and the subjective evaluation of post-operative clinical outcome. The patient's body mass index (BMI) had no effect on the outcome, but the majority of our patients had a BMI below 30 (average, 28.2). The range of motion after surgery was not significantly limited. Both the occurrence of complications and alignment maintenance are comparable with the results of distraction osteotomy. CONCLUSIONS The mid-term results of valgus osteotomy performed by the technique described by Coventry et al. testify to the lasting success of this method. Satisfaction with its outcome can be expected in about 90% of the patients in a 5-year post-operative period. To achieve this, it is necessary to strictly observe the indication criteria, operative technique and thorough arthroscopic treatment of the joint. Also, the necessity of slight over-correction to 8 degrees of valgus is emphasised.
Keywords: dospělí; Internal Fixators; bérec; Female; interní fixátory; kloubní deformity získané; Adult; Leg; výsledek terapie; mladý dospělý; ženské pohlaví; Osteotomy; lidé; Joint Deformities, Acquired; Treatment Outcome; artróza kolenních kloubů; osteotomie; Male; Young Adult; Osteoarthritis, Knee; lidé středního věku; mužské pohlaví; Middle Aged; Humans